Aplicación del modelo factorial para identificar las causas y efectos del comercio informal. - Quispe Fernandez, Gabith Miriam; Villa Villa, Marlon Vicente; Velarde, Rodrigo (Universidad Técnica de Machala, 2019)
The objective of the research determines the causes and effects of informal trade in the case of Ecuador - City of Riobamba. It uses the inductive method as a methodology, it is of a causal - statistical level. The population corresponds to 3,600 merchants and the survey is applied to a sample of 310. The multivariate factorization and linear regression analysis is applied. The results of the research show that the relationship of informal trade activity is not significant with the variables, such as marital status, age, economic income and educational level. Likewise, it is determined through the factorial analysis, the prices of the products, the migration, the payment of taxes, the basic necessities, the availability of public spaces, the factors that affect the activity although they are not observed as determining variables. Therefore, it is concluded that informal trade is related to the general characteristics of the population and commercial activity; and generates as a consequence the reduction in tax collection
El objetivo de la investigación determina las causas y efectos del comercio informal aplicado al caso de Ecuador - Ciudad de Riobamba. Usa como metodología el método inductivo, es de un nivel causal – estadístico. La población corresponde a 3.600 comerciantes y se aplicó la encuesta a una muestra de 310. Se aplica el análisis multivariante de factorización y regresión lineal. Los resultados de la investigación muestran que la relación de la actividad del comercio informal no es significativa con las variables, como el estado civil, edad, ingreso económico y el nivel de instrucción. Asimismo, se determina a través del análisis factorial, los precios de los productos, la migración, el pago de impuestos, las necesidades básicas, la disponibilidad de espacios públicos son los principales factores que inciden en la actividad aunque no se observan como variables determinantes. Por tanto, se concluye que el comercio informal se relaciona con las características generales de población y de la actividad comercial; y genera como consecuencia la reducción en la recaudación de impuestos.
Keywords: COMERCIO INFORMAL; ANÁLISIS MULTIVARIANTE; FACTORES